Integrating information and communication technology into nursing practice for resilience: A cross-sectional quantitative study - Li-Fang Chang; Pi-Hsia Lee; Dawn Dowding; Chia-Jung Hsieh; Kuei-Ru Chou; Tso-Ying Lee (PLoS ONE, 2025)
Background The adoption of information and communication technology (ICT) tools was accelerated by the COVID-19 pandemic to facilitate contactless interaction and reduce infection risk. However, there remains a lack of quantitative analysis regarding nurses’ perceptions and experience with these ICT tools. Purpose This survey study aimed to assess nurses’ experience and satisfaction with ICT tools during the COVID-19 pandemic. Methods Registered nurses were recruited into this questionnaire-based cross-sectional study. Questions about organizational ICT training and support, impact on patient care, and ICT perception were asked. Results A total of 237 nurses completed and returned the questionnaire. The majority of nurses reported that ICT tools support instant consultation and communication with patients (62.0%). ICT tools’ suitability and effectiveness of features were 6.40 ± 1.72 and 6.10 ± 1.73, respectively. Nurses’ attitudes and perceived benefits of the ICT tools scored 3.59 ± 0.81 and 3.52 ± 0.87, respectively. The mean system usability score was 52.75 ± 11.75. Subgroup analyses highlighted the influence of ICT training, support, concerns about patient safety, and user anxiousness on the scores. Conclusion Participants identified equipment, infrastructure, and workflow changes as major issues in ICT use, which require organizational efforts for improvement. Addressing data utility and security concerns through policy initiatives is also imperative. This study highlights the necessity of organizational initiatives to promote good use of ICT tools and to enhance nursing resilience, especially when facing a health emergency, more resources should be allocated to the IT department that aims to respond soon; strategies including integrating digital tools for emergencies into other established systems, expanding the size of IT team for maintenance and providing training course with multiple modules.